Transcription factor Sp3 antagonizes activation of the ornithine decarboxylase promoter by Sp1. - Kumar, A P (1997)
Ornithine decarboxylase (ODC) expression is important for proliferation and is elevated in many tumor cells. We previously showed that Sp1 is a major positive regulator of ODC transcription. In this paper we have investigated transcriptional regulation of rat ODC by the closely related factor Sp3. While over-expression of Sp1 caused a dramatic activation of the ODC promoter, over-expression of Sp3 caused little or no activation in either Drosophila SL2 cells (lacking endogenous Sp1 or Sp3) or in H35 rat hepatoma cells. Furthermore, co-transfection studies demonstrated that Sp3 abolished trans -activation of the ODC promoter by Sp1. DNase I footprint studies and electrophoretic mobility shift assays demonstrated that both recombinant Sp1 and Sp3 bind specifically to several sites within the ODC promoter also protected by nuclear extracts, including overlapping GC and CT motifs located between -116 and -104. This CT element is a site of negative ODC regulation. Mutation of either element reduced binding, but mutation of both sites was required to eliminate binding of either Sp1 or Sp3. These results demonstrate that ODC is positively regulated by Sp1 and negatively regulated by Sp3, suggesting that the ratio of these transcription factors may be an important determinant of ODC expression during development or transformation.